PENGARUH KECEMASAN TERHADAP PROBLEM SOLVING MAHASISWA AKHIR BIMBINGAN DAN KONSELING UNIVERSITAS ISLAM NEGERI SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Helma Yulia Putri; M. Arif; Yeni Afrida; Elviana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the phenomenon that occurs in students who experience high levels of anxiety, which tends to reduce the effectiveness of problem solving, because individuals have difficulty concentrating, experience memory decline, and tend to avoid problems. This study aims to determine the extent of anxiety’s influence on the problem solving of final year guidance and counseling students. The research method used in this study is a quantitative descriptive method, with a stratified random sampling technique. The study pupulation consisted of 327 students, with a sample size of 126 students. The instruments used in this study were anxiety and problem solving quetionnaires developed by the research. Data analysis used to test the research hypothesis included simple linear regression, the f test, and the coefficient of determination. The results of the data analysis showed a significant effect of anxiety on student problem solving, wut a significance value of 11.6%. this indicates that anxiety contributes to the problem solving abilities of final year students, albeit in the weak category.